Circular energy integration: Optimization of refuse derived fuel pellets and residual heat recovery for industrial decarbonization - Khalisha Aura Kartika; Qurrotul A’yun; Yilen Yustika (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Indonesia's industrial sector contributes 36% to national carbon emissions with 30-60% of thermal energy wasted as residual heat, while 68.5 million tons of waste per year, 60-70% of which is inorganic waste, is not managed optimally. Methods: This study used a literature review method with a systematic approach to examine and analyze the circular energy integration system. The literature sources used included Scopus and Web of Science indexed international journals, accredited national journals, reference books, and policy and regulatory documents related to waste and energy management in Indonesia. Findings: This system combines three main components, namely the production of RDF pellets from inorganic waste, the recovery of residual heat from industrial processes, and a real-time emission monitoring system to ensure environmental compliance. The integration of these three components creates synergies that not only reduce waste volume and greenhouse gas emissions but also produce alternative energy that can substitute fossil fuels in industrial applications. Conclusion: This study suggests that system integration can assist in implementing industrial decarbonization. Novelty/Originality of this article: The innovative aspect presented is the integration of RDF Pellets as co-firing with the utilization of residual heat in boilers so that it can be fully utilized.